The crystal structure of dichlorido-bis(3-methyl-3-imidazolium-1-ylpropionato-κ2)-cadmium(II), C14H20CdCl2N4O4 - Yang Fei; Wang Zongwei; Liu Pengju; Guo Libing; Xian Dong (Zeitschrift für Kristallographie - New Crystal Structures)
C14H20CdCl2N4O4, monoclinic, P21/n (no. 14), a = 8.261(3) Å, b = 16.390(5) Å, c = 13.967(4) Å, β = 95.850(4)°, V = 1881.3(10) Å3, Z = 4, Rgt(F) = 0.0342, wRref(F2) = 0.0873, T = 296 K.